Pengaruh Keterampilan Kerja Terhadap Kesiapan Kerja Siswa SMK Negeri 1 Tondano - Kandoli, Louisa Nicolina (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze: 1) the influence of hard skills on job readiness at SMK N 1 Tondano, 2) the influence of soft skills on job readiness at SMK N 1 Tondano, 3) the influence of 4C skills on job readiness at SMK N 1 Tondano, 4) There is a significant simultaneous influence between hard skills, soft skills, and 4C skills on job readiness at SMK N 1 Tondano students. The research design is quantitative with a correlational research approach, using simple and multiple regression analysis. The results of the study are: 1) there is a significant influence between hard skills on job readiness at SMK N 1 Tondano, contributing 13.76%. 2) there is a significant influence between soft skills on job readiness at SMK N 1 Tondano, contributing 10.82%. 3) There is a significant influence between 4C skills on the work readiness of State Vocational High School 1 Tondano, which contributes 19.36%. 4) There is a simultaneous significant influence between hard skills, soft skills, and 4C skills on the work readiness of students of State Vocational High School 1 Tondano, which contributes 26.01%. Thus it can be concluded: that the improvement of hard skills, soft skills, and 4C skills includes critical thinking skills, problem solving, time management, to the ability to deal with pressure, communication skills, teamwork, adaptability, and work ethics of critical thinking, creativity, collaboration, and communication is expected to improve work readiness in the form of critical thinking skills, problem solving, time management, to the ability to deal with pressure, discipline, and responsibility in work. Or in improving work readiness must pay attention to hard skills, soft skills, and 4C skills that actually provide a meaningful contribution. With the existence of conducive hard skills, soft skills, and 4C skills, it is hoped that they will be able to provide maximum work readiness for students. In other words, having a high level of hard skills, soft skills, and the 4Cs can foster good or high levels of student job readiness.